2016
DOI: 10.1016/j.jor.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Megaprostheses in the management of trauma of the knee

Abstract: Conclusion:A megaprosthesis is a viable option in complex fractures around the knee.Crown

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Originally designed to treat oncological bone loss, the megaprosthesis is now generally used to reconstruct large skeletal defects. However, the indications for this device have expanded to include complex trauma, multiply failed osteosynthesis, and infection [4,5]. Systemic antibiotics are often insufficient to treat implant-related infection effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Originally designed to treat oncological bone loss, the megaprosthesis is now generally used to reconstruct large skeletal defects. However, the indications for this device have expanded to include complex trauma, multiply failed osteosynthesis, and infection [4,5]. Systemic antibiotics are often insufficient to treat implant-related infection effectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, we would like to point out the importance of having a team of experienced surgeons, accustomed to using this type of implant and to filling large segmental defects (for example in oncological orthopedic surgery) (Fig. 2) 42 .…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, the incidence of failure is mostly at 48–72 month post implantation [ 13 ]. Evans et al also reported after three years of follow up no patient, from total of 10 patients, had prosthetic failure [ 14 ]. Longer survival was reported by Biau et al where median of mega prosthesis survival rate was up to 130 months following femoral resection and 117 months following median resection [ 4 ].…”
Section: Discussionmentioning
confidence: 99%